Analisis Perbandingan Metode Single Exponential Smoothing dan Single Moving Average dalam Peramalan Pemesanan - Ni Putu Linda Santiari; I Gede Surya Rahayuda (Teknik Informatika Universitas Pamulang, 2021)
ACK Fried Chicken (Ayam Crispy Kriuk) is a local fast food business that provides food and beverages. The competition for chicken franchises in Bali and the number of orders made by customers through online applications, namely the Gofood and Grabfood applications on ACK Fried Chicken, has resulted in the importance of implementing the SCM strategy in ACK Fried Chicken, to maintain customer trust and satisfaction. By providing an overview to make estimates in the present for future production, it is necessary to forecast demand which is carried out using the forecasting method. The forecasting method used is the time series method, namely the Single Exponential Smoothing method and the Single Moving Average method. Forecasting using the time series method, namely SES and SMA, the forecasting model is obtained from the actual data used in this case study, the forecasting model using the SMA method is declared very good because it has a MAPE value <10% while the SES method is declared good because it has a MAPE value. = 11% (10-20%). The SMA method has an error rate that is more sophisticated than the SES method. For forecasting order requests in this study, the SMA method is better used because it has the smallest error rate in forecasting.